Maximum Gauge Pressure in Dangerous Goods Packagings Under Normal Conditions of Carriage – Comparison of Direct Measurement and Calculation. (18th November 2014) - Schlick‐Hasper, Eva; Bethke, John; Jahnke, Wolfgang; Drousch, Björn; Goedecke, Thomas; Kraume, Matthias
<x xml:space="preserve">Abstract</x> The objective of this work was to determine the maximum gauge pressure in the vapour phase above the liquid in different design types of dangerous goods packagings under normal conditions of carriage. The design types investigated were steel and plastic packagings with a volume of approximately 6 l. Two different methods were applied. In method 1, the pressure inside the packaging filled with a certain filling substance (dichloromethane) was directly measured under simulated conditions of carriage (degree of filling: 90%; filling temperature: 15°C; temperature during storage: 31°C). The maximum measured gauge pressures were between 89 mbar for a light plastic jerrican and 336 mbar for a steel drum. In method 2, the gauge pressure was calculated. The consideration of a rigid packaging combined with the assumption of a vapour pressure of zero during filling and sealing can serve as a worst case scenario. The calculated gauge pressure is approximately 1061 mbar. This procedure leads to the highest safety factor and does not require any experimental investigations. For a more realistic approximation of the gauge pressure of a non‐rigid packaging, a packaging‐specific function of relative expansion can be used, which is determined by a hydraulic pressure test. The calculated values ranged from 105 to 347 mbar. Method 2 provides conservative results. No hazardous filling substance is needed, and it allows a prediction of gauge pressure for other temperatures, substances and filling degrees. Therefore, this method could serve as alternative to UN Model Regulations 6.1.5.5.4 (a). Copyright © 2014 John Wiley & Sons, Ltd.